2023
DOI: 10.1186/s13195-023-01190-0
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of and recommendations on clinical trial design in Alzheimer’s disease from the participant’s point of view: a mixed-methods study in two clinical trial centers in the Netherlands

Abstract: Introduction In the context of the development of pharmaceutical interventions, expectations and experiences of participants are essential. Their insights may be particularly helpful to address the challenges of recruiting and retaining participants for Alzheimer’s disease (AD) clinical trials. We examined clinical trial participants’ experiences to optimize trial design in Alzheimer’s disease (AD). Method In this mixed-methods study, we included a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Previous authors have suggested one of the reasons RCTs in AD have been largely unsuccessful is because of poor trial design. 28 There has been substantial work on methods to improve RCT design including research on participants' priorities to increase willingness to participate in RCTs, 29 suggestions to use Bayesian adaptive RCT designs, 30 and using polygenic hazard scores to stratify participants. 31 However, limited consideration has been given to the age of participants when they enter into an RCT and the accepted convention is to enroll partic-ipants over 50, 60, or 65 years to 85 years old depending on the target population, study aims or choice of outcome measure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have suggested one of the reasons RCTs in AD have been largely unsuccessful is because of poor trial design. 28 There has been substantial work on methods to improve RCT design including research on participants' priorities to increase willingness to participate in RCTs, 29 suggestions to use Bayesian adaptive RCT designs, 30 and using polygenic hazard scores to stratify participants. 31 However, limited consideration has been given to the age of participants when they enter into an RCT and the accepted convention is to enroll partic-ipants over 50, 60, or 65 years to 85 years old depending on the target population, study aims or choice of outcome measure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a previous study observed an association between the number of retention tactics used at NIHfunded ADRCs and rates of retention at 1 and 2 years [14]. Trials that require longer participation may also benefit from adjusting other study design features like reducing/replacing high-burden assessments (e.g., lumbar puncture) and increasing motivating factors such as returning test results [15] and even financial bonuses for trial completion [16].…”
Section: Discussionmentioning
confidence: 99%